Gombrowicz wobec "wielkości" - Fiszbak, Zbigniew (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The article deals with Witold Gombrowicz’s autocreational efforts to bring the readers and critics to believe in his own uniqueness, greatness and genius. In Gombrowicz’s opinion literature, having its roots in pure artistic contemplation, is also a fight of writer to establish his position among others. Author of Diary takes it as a rule to “ self-mitologize” in his receivers minds and according to this rule he ostentatiously makes a great writer of himself. When his writing at last achievers true recognition and acclaim, he tries in turn to depreciate his strategy.